Analisis faktor ibu terhadap kejadian stunting pada balita usia 24-59 bulan di perkotaan - Elya Sugianti; Annas Buanasita; Henny Hidayanti; Berliana Devianti Putri (AcTion: Aceh Nutrition Journal, 2023)
The prevalence of stunting is still high in urban areas. Maternal factors such as height, education, occupation, antenatal visits, and nutritional status have increased stunting in urban areas. The study aims to analyze the maternal factors that influence the incidence of stunting among children aged 24-59 months in urban areas. The case-control design study was conducted in May-July 2019 in Pasuruan City. Samples of 67 cases (HAZ < -2SD) and 67 controls (HAZ > -2SD) were selected by simple random sampling. Data on children's age, gender, birth order, education, occupation, pregnancy classes, and antenatal visits were collected by interviewing respondents using a questionnaire. Data on birth weight, maternal age during pregnancy, maternal upper arm circumference during pregnancy, and maternal height were obtained from the MCH Handbook. The chi-square test and Logistic Regression were used for data analysis. The results showed that the maternal nutritional status during pregnancy was associated with the incidence of stunting in urban areas (p= 0,010). In contrast, children's age, gender, birth order, birth weight, maternal age during pregnancy, maternal height, education, occupation, pregnancy classes, and antenatal visits were not associated (p> 0,05). The incidence of stunting was 3,37 times higher in mothers with MUAC < 23,5 cm during pregnancy (OR= 3,37). In conclusion, maternal nutritional status during pregnancy is the main predictor of stunting among children aged 24-59 months in urban areas.